2015
DOI: 10.1109/lawp.2014.2388075
|View full text |Cite
|
Sign up to set email alerts
|

Circularly Polarized Dielectric Resonator Antenna Fed by Off-Centered Microstrip Line for 2.4-GHz ISM Band Applications

Abstract: A special feeding technique of an off-centered microstrip feedline slot-coupled circularly polarized (CP) cylindrical dielectric resonator antenna (DRA) for 2.4-GHz industry, science and medicine (ISM) band applications is reported in this letter. Good CP characteristics can be achieved using two coupling points with a quarter-wavelength path difference and 90° phase shift, resulting in a series feeding circuitry. The 10-dB impedance bandwidth and the 3-dB axial ratio of the proposed antenna are 141 and 85 MHz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…Literature survey reveals that the generation of orthogonal modes depends on either geometry of dielectric resonator or particular feeding mechanisms and it may be single, dual, or sequentially feeding techniques . The single feeding is more favorable in the antenna community for exciting the antenna structure because it has advantages like less complexity and flexibility to excite DRA for generation of CP waves . There are several different types of dielectric resonator (DR) geometries have been utilized to generate CP bandwidth by using a different combination of single feeding technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature survey reveals that the generation of orthogonal modes depends on either geometry of dielectric resonator or particular feeding mechanisms and it may be single, dual, or sequentially feeding techniques . The single feeding is more favorable in the antenna community for exciting the antenna structure because it has advantages like less complexity and flexibility to excite DRA for generation of CP waves . There are several different types of dielectric resonator (DR) geometries have been utilized to generate CP bandwidth by using a different combination of single feeding technique.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] The single feeding is more favorable in the antenna community for exciting the antenna structure because it has advantages like less complexity and flexibility to excite DRA for generation of CP waves. [6][7][8] There are several different types of dielectric resonator (DR) geometries have been utilized to generate CP bandwidth by using a different combination of single feeding technique.…”
Section: Introductionmentioning
confidence: 99%
“…Table provides the technical performance comparison between the proposed antenna and previously published related antenna structures in the literature at around 2.4 GHz band applications. It is observed that the proposed antenna has good performances in terms of the antenna complexity, size, polarization, impedance bandwidth, and ARBW.…”
Section: Resultsmentioning
confidence: 99%
“…A microstrip‐line‐fed microstrip slot antenna has also shown wide‐band and UWB performance . Some of them reported the UWB antenna with CP but they have a narrow 3‐dB axial ratio BW . The comparative lists for the performance of some similar antennas and the proposed antenna are shown in Table .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Some of them reported the UWB antenna with CP but they have a narrow 3-dB axial ratio BW. [15][16][17][18][19][20][21][22][23][24][25][26] The comparative lists for the performance of some similar antennas and the proposed antenna are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%